LiDAR Based Obstacle detection for Snow Groomers. Issue 2 (2020) - Onesto, L.; Corno, M.; Franceschetti, L.; Hokka, E.; Savaresi, S.M.
Abstract: This paper presents an obstacle detection system for snow groomers. The system is based on a 2D solid-states LiDAR sensor mounted on the top of the cabin. The measurements describe the surrounding environment through an Occupancy Grid framework, which is extended for this particular case study. The proposed approach set the occupancy probability of the surrounding environment based on the expected height of the obstacle. The method is extensively analyzed through experimental test on a snow groomer.